Effects of Doping on the Performance of CuMnOx Catalyst for CO Oxidation - Subhashish Dey; Ganesh Chandra Dhal; Ram Prasad; Devendra Mohan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
The rare earth-doped CuMnOx catalysts were prepared by co-precipitation method. The CuMnOx catalyst was doped with (1.5 wt.%) CeOx, (1.0 wt.%) AgOx, and (0.5 wt.%) of AuOx by the dry deposition method. After the precipitation, filtration, and washing process, drying the sample at 110 oC for 16 hr in an oven and calcined at 300 oC temperature for 2 h in the furnace at stagnant air calcination condition. The influence of doping on the structural properties of the catalyst has enhanced the activity of the catalyst for CO oxidation. The doping of noble metals was not affected the crystal structure of the CuMnOx catalyst but changed the planar spacing, adsorption performance, and reaction performance. The catalysts were characterized by Brunauer-Emmett-Teller (BET) surface are, Scanning Electron Microscope Energy Dispersive X-ray (SEM-EDX), X-Ray Diffraction (XRD), and Fourier Transform Infra Red (FTIR) techniques. The results showed that doping metal oxides (AgOx, AuOx, and CeOx) into CuMnOx catalyst can enhance the CO adsorption ability of the catalyst which was confirmed by different types of characterization technique.